THE REAL WINNERS : APLIKASI KNOWLEDGE MANAGEMENT DALAM INDUSTRI PERBANKAN NASIONAL - Yuliyanto, Heri (UI Scholars Hub, 2016)
Mastery of information technology is important for the banking industry has an oligopoly market structure, but does not guarantee a sustainable competitive advantage. To win the competition is not only determined by the technologically and price (interest given), but also factors mastery of knowledge and information currently an issue that is very strategic. If a bank uses technology as an advantage its competitiveness, then the advantage will be temporary, because the technology has the properties easily imitated. However, if the advantages of information technology along with the mastery of information and knowledge of quality management, the competitors require greater effort and a long time to be able to imitate or duplicate the competitive advantage. Thus the competitive advantage that will last longer. Through literature study and analysis of secondary data obtained information that the national banking market outlook is still widespread. In addition, the technology factor is not the major factor is the main attraction or reason for customers to have a bank account, but the image bank safe is the main reason to have accounts.